2016
DOI: 10.1007/s10735-016-9697-9
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent impact of inferior alveolar nerve transection on mandibular bone metabolism and the underlying mechanisms

Abstract: Aging is associated with peripheral nerve degradation and bone destruction. The aim of the study is to elucidate the influence of sensory denervation on bone metabolism in different age groups by establishing a modified unilateral inferior alveolar nerve transection (IANT) model. The rats, divided into young, middle-aged and aged group, were sacrificed at 1, 2, 4 and 8 weeks after right IANT. The histological changes of mandibles were analyzed by fluorescent double labeling, micro-CT, HE, TRAP and anti-CGRP im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 33 publications
1
15
1
Order By: Relevance
“…Previously, we observed that IANT led to the breakdown of the distal nerve endings, triggered an acute neuropeptide shortage, and resulted in a sharp increase in the nociceptive threshold . In the current study, surgical sensory denervation triggered a disturbance of normal bone remodeling involving the bone formation rate (Fig.…”
Section: Resultssupporting
confidence: 58%
See 4 more Smart Citations
“…Previously, we observed that IANT led to the breakdown of the distal nerve endings, triggered an acute neuropeptide shortage, and resulted in a sharp increase in the nociceptive threshold . In the current study, surgical sensory denervation triggered a disturbance of normal bone remodeling involving the bone formation rate (Fig.…”
Section: Resultssupporting
confidence: 58%
“…Thirty‐six 20‐week‐old male C57Bl/6J mice were acclimated for 1 week before surgery. A sensory denervation model was performed in the current study. Briefly, a skin incision along the middle one‐third of the lower mandible margin was performed after anesthetization.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations